2017
DOI: 10.1088/1361-6455/aa5b20
|View full text |Cite
|
Sign up to set email alerts
|

The higher-order blackbody-radiation shift of atomic energy levels

Abstract: The one-loop correction and two-loop contribution to black-body radiation (BBR) shift are restudied. The S-matrix approach and nonrelativistic quantum electrodynamics (NRQED) are adopted in finite temperature case. The relativistic correction to one-loop BBR-shift has a (Zα) 2 αT 2 /m-order contribution. In the two-loop case, the pure thermal (real) photon part is too tiny to be detected; while the corrections induced by the thermal and virtual mixing diagram are at (Zα) 2 α 2 T 2 /m order. We calculate the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…On example of thermal self-energy correction it was established that the regularization procedure suggested in this work gives a physical result. Namely, in opposite, for example, to the results of (Zhou et al, 2017) there are no 'adventitious' contributions besides the Stark shift and BBR induced level width. Latter have a simple analogy with the QM results and 'ordinary' zero vacuum QED case when the real part of one-loop self-energy correction represents the energy shift and the imaginary parts corresponds to the lifetime of atomic level, see (Labzowsky et al, 1993).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…On example of thermal self-energy correction it was established that the regularization procedure suggested in this work gives a physical result. Namely, in opposite, for example, to the results of (Zhou et al, 2017) there are no 'adventitious' contributions besides the Stark shift and BBR induced level width. Latter have a simple analogy with the QM results and 'ordinary' zero vacuum QED case when the real part of one-loop self-energy correction represents the energy shift and the imaginary parts corresponds to the lifetime of atomic level, see (Labzowsky et al, 1993).…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, the results arising from the one-loop thermal self-energy correction have a clear physics which originally was found within the Quantum Mechanical approach. This circumstance has a most significant conclusion: a) the renormalization or regularization procedure described in section III.C is justified in this case also; b) besides the Stark shift anf level broadening there are no other 'artificial' contributions depending on temperature, see for example (Escobedo andSoto, 2008, 2010;Zhou et al, 2017).…”
Section: One-loop Self-energy Correction In Thermal Coulomb Gaugementioning
confidence: 87%
See 1 more Smart Citation
“…The BBR is isotropic and thus it can be described by the scalar polarizability. Some studies on BBR shifts to atomic energy levels can be found in [11,[14][15][16][17], including relativistic and QED corrections. Here we only focus on the nonrelativistic energy shift due to the BBR, which is given by…”
Section: Application On Blackbody Radiation Shiftmentioning
confidence: 99%
“…In the nonrelativistic limit, the BBR shift acts as T 4 /Z 4 ; whereas the relativistic correction acts as (ZαT ) 2 . Therefore, the relativistic correction becomes more important for high Z and/or low T [11,17].…”
Section: Application On Blackbody Radiation Shiftmentioning
confidence: 99%